Allopurinol and the incidence of bladder cancer: a Taiwan national retrospective cohort study. Issue 3 (May 2016) - Chen, Chung-Jen; Hsieh, Ming-Chia; Liao, Wei-Ting; Chan, Ya-Ting; Chang, Shun-Jen
Abstract : Our aim is to investigate the risk association between allopurinol use and cancer incidence among gout patients using clinical evidence. Newly diagnosed male patients with gout, 20 years or older, were included after excluding those who had a diagnosis of type 2 diabetes, and were followed up for 12 years in a retrospective cohort study of one million outpatients of a national database. The gout patients were matched to male controls by age and first diagnosis date of gout disease. We then estimated the risk associations between incident cancers and duration of allopurinol use by Cox hazard regression, age-adjusted standardized incidence ratio, and incidence per 1000 person-years. A total of 24 050 gout patients and 76 129 controls were included. The incidence of all-cause cancers for gout patients and controls was 8.26 cases and 7.49 cases/1000 person-years, respectively; it was markedly increased in gout patients who used allopurinol for over 90 days. The hazard ratio of all-cause cancers was 1.21 (95% confidence interval=1.03–1.42, P =0.019) after adjustment for age and 2.26 for bladder cancer (95% confidence interval=1.32–3.87, P =0.003) on comparing those who used allopurinol for over 90 days with nonusers. Meanwhile, other cancers did not show the same significant result. We concluded that those who used allopurinol for a long duration had a higher occurrence of both bladder cancer and all-cause cancers in clinical evidence. Abstract : Supplemental Digital Content is available in the text.